Terms and expressions, beliefs and practices for different occassions of the Tagalogs of Pasig, Baras, and Morong, Rizal - Ferrer, Angelina J. 1930- ([Quezon City s.n.], 1972)
The terms and expressions, beliefs and practices for different occasions of the Tagalogs Pasig, Baras, and Morong, Rizal were covered in this study. It attempted to find 1) how the terms and expressions for the different occasions differ among the Tagalogs of Pasig, Baras and Morong, 2) how words with similar meaning differ in form from one place to another, 3) how words of similar form differ in meaning from one place to another and, 4)the significance in learning these differences in a given place.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Pilipino language -- Terms and phrases; Tagalogs -- Social life and customs